Micro-arc and thermal oxidized titanium matrix composites for tribocorrosion-resistant biomedical implants - Sousa, Luís (2024)
Superior tribocorrosion resistance is offered by titanium matrix composites (TMCs) compared to their unreinforced matrix metal, but bioactivity concerns are raised for biomedical applications. Simple methods such as micro-arc oxidation (MAO) and thermal oxidation (TO) are employed to enhance the bioactivity and degradation resistance of Ti. However, the impact of those surface treatments on TMC surfaces is poorly understood. Therefore, the present work aimed to explore the influence of MAO and TO treatments on the surfaces of in-situ Ti-TiB-TiC and ex-situ Ti-B4C composites, and to assess their corrosion and tribocorrosion performance. Corrosion and tribocorrosion tests were conducted in phosphate-buffered saline solution (PBS) at body temperature. Electrochemical assays were performed by means of potentiodynamic polarization scans while additional potentiostatic tests were performed for the untreated ex-situ composites. Tribo-electrochemical assays were conducted under open circuit potential (OCP) and under normal loads of 0.5 and 10 N against a 10 mm diameter alumina ball in a reciprocating ball-on-plate tribometer. Results revealed reinforcement detachments in ex-situ composites after both treatments. This was primarily attributed to oxide layer growth at the reinforcement/reaction zone interface. Hence, the use of MAO and TO on ex-situ Ti-B4C composites may not be appropriate for biomedical applications, mainly because the B4C particles tend to detach during the treatment. In contrast, TO-treated in-situ composites displayed excellent combination of corrosion and tribocorrosion performance, even under elevated applied loads, mainly due to the existence of the oxygen diffusion zone (ODZ) beneath the oxide surface produced by TO, together with the more stable electrochemical properties observed during steady-state conditions.